solve this please....
Attachments:
![](https://hi-static.z-dn.net/files/d7f/00d761a8e7c57f1d58d036aae535b8a8.jpg)
Answers
Answered by
1
tan ^ -1 ( 1/ ( 1 + n( n+1))
tan^ -1 ( n+1 - n)/ 1 + n ( n+1))
As tan^ -1( x -y)/ 1 + xy = tan^ -1 x - tan^-1 y
So tan^ -1 ( n +1) - tan^ -1 (n)
So
tan^ -1 (2) - tan^ -1 (1)+ tan^ -1( 3) - tan^ -1( 2)
+ tan^ -1( 4) - tan^-1( 3).........tan^ -1( n+1) - tan^ -1(n)
So it will give - tan^ -1 (1)+ tan^ -1( n+1) = tan^-1@
tan^ -1( n +1 -1)/ 1 + n+1)= tan^-1@
tan^ -1 ( n)/ 2 +n = tan^ -1 @
compare
n/ ( 2 + n)= @
tan^ -1 ( n+1 - n)/ 1 + n ( n+1))
As tan^ -1( x -y)/ 1 + xy = tan^ -1 x - tan^-1 y
So tan^ -1 ( n +1) - tan^ -1 (n)
So
tan^ -1 (2) - tan^ -1 (1)+ tan^ -1( 3) - tan^ -1( 2)
+ tan^ -1( 4) - tan^-1( 3).........tan^ -1( n+1) - tan^ -1(n)
So it will give - tan^ -1 (1)+ tan^ -1( n+1) = tan^-1@
tan^ -1( n +1 -1)/ 1 + n+1)= tan^-1@
tan^ -1 ( n)/ 2 +n = tan^ -1 @
compare
n/ ( 2 + n)= @
Similar questions
Math,
8 months ago
Computer Science,
8 months ago
Science,
8 months ago
CBSE BOARD X,
1 year ago
Art,
1 year ago
Biology,
1 year ago
Biology,
1 year ago